2016
DOI: 10.1007/s00384-016-2681-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of restless legs syndrome in patients with inflammatory bowel disease on sleep, fatigue, and quality of life

Abstract: Sleep disorders including longer sleep latency, shorter sleep duration, and fatigue are characteristic symptoms of restless legs syndrome in inflammatory bowel disease patients, resulting in worse health-related quality of life. Therefore, clinicians treating patients with inflammatory bowel disease should be alert for restless legs syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
7
0
6
Order By: Relevance
“…Sleep problems of patients include short sleep time, difficulty in falling asleep, increased number of WASO, etc (26). Summarizing their research, the factors affecting sleep quality of IBD patients include disease active period, unemployment, female, hormone therapy, restless legs syndrome, fatigue, anxiety, inflammatory factors, and so on (16,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep problems of patients include short sleep time, difficulty in falling asleep, increased number of WASO, etc (26). Summarizing their research, the factors affecting sleep quality of IBD patients include disease active period, unemployment, female, hormone therapy, restless legs syndrome, fatigue, anxiety, inflammatory factors, and so on (16,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies showed the increased frequency of RLS and its association with poor sleep quality in many diseases such as chronic renal failure, [26] fibromyalgia, [27] ankylosing spondylitis, [28] lumbar radiculopathy, [29] inf lammatory bowel disease, [30] or primary biliary cirrhosis. [31] However, there exist only a small number of studies which investigate the relationship between RLS and allergic diseases in adults, but not in children.…”
Section: Discussionmentioning
confidence: 99%
“…In an adult Japanese study, Uemura et al [22] reported that QoL scores were significantly lower in patients with any sleep disturbance than in patients without sleep disturbance. Another study in adults showed that sleep disorders, which included longer sleep latency, shorter sleep duration and fatigue, are characteristic symptoms of restless legs syndrome in IBD patients, resulting in worse QoL [23]. This pediatric study showed that the adolescent sleep questionnaires significantly correlated with QoL and psychosocial functioning scores.…”
Section: Discussionmentioning
confidence: 78%